Inflation Targeting And Credibility Of Central Banks: What For The Bank Of Algeria? - Fekir, Hamza (جامعة الوادي - University of Eloued, 2022)
In recent years the monetary strategy of inflation targeting has received a great deal of attention and has been the subject of much debate among experts on monetary policy issues. This article aims mainly, the presentation of this monetary strategy, and above all, highlight the positive economic performances of the central banks having adopted it. In view of these positive results achieved by these central banks, we also wonder about the feasibility of adopting it by the Bank of Algeria.
مقال
Keywords: Currency ; Inflation ; Monetary Policy ; Central Bank ; Credibility ; Inflation targeting